CpxR regulates the Rcs phosphorelay system in controlling the Ysc-Yop type III secretion system in Yersinia pseudotuberculosis. Issue 1 (9th January 2021) - Fei, Keke; Chao, Hong-Jun; Hu, Yangbo; Francis, Matthew S.; Chen, Shiyun
Abstract : The CpxRA two-component regulatory system and the Rcs phosphorelay system are both employed by the Enterobacteriaceae family to preserve bacterial envelope integrity and function when growing under stress. Although both systems regulate several overlapping physiological processes, evidence demonstrating a molecular connection between Cpx and Rcs signalling outputs is scarce. Here, we show that CpxR negatively regulates the transcription of the rcsB gene in the Rcs phosphorelay system in Yersinia pseudotuberculosis . Interestingly, transcription of rcsB is under the control of three promoters, which were all repressed by CpxR. Critically, synthetic activation of Cpx signalling through mislocalization of the NlpE lipoprotein to the inner membrane resulted in an active form of CpxR that repressed activity of rcsB promoters. On the other hand, a site-directed mutation of the phosphorylation site at residue 51 in CpxR generated an inactive non-phosphorylated variant that was unable to regulate output from these rcsB promoters. Importantly, CpxR-mediated inhibition of rcsB transcription in turn restricted activation of the Ysc-Yop type III secretion system (T3SS). Moreover, active CpxR blocks zinc-mediated activation of Rcs signalling and the subsequent activation of lcrF transcription. Our results demonstrate a novel regulatory cascade linking CpxR-RcsB-LcrF to control production of the Ysc-Yop T3SS.